Asperger's Disorder - Heidi Liss Radunovich; Keith Gouin (EDIS, 2007)
FCS2276, a 4-page factsheet by Heidi Liss Radunovich and Keith Gouin, describes Asperger's Disorder, a disorder on the autism spectrum that affects social behavior and interaction. It gives information on how the disorder typically presents and lets parents knows what to do if they think their child may have the disorder. Published by the UF Department of Family, Youth and Community Sciences, September 2007.